2015
DOI: 10.1371/journal.pone.0124586
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Association between Tobacco Smoking and Central Obesity among 0.5 Million Chinese People: The China Kadoorie Biobank Study

Abstract: ObjectivesLifestyle factors are well-known important modifiable risk factors for obesity; the association between tobacco smoking and central obesity, however, is largely unknown in the Chinese population. This study examined the relationship between smoking and central obesity in 0.5 million Chinese adults, a population with a low prevalence of general obesity, but a high prevalence of central obesity.SubjectsA total of 487,527 adults (200,564 males and 286,963 females), aged 30-79 years, were enrolled in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
55
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 41 publications
11
55
1
1
Order By: Relevance
“…A recent large cohort study in the Chinese adult population has also shown that tobacco smoking is an important risk factor for central obesity. However, the positive association of regular smoking with WC was observed especially in male normal-weight adults after adjustment for BMI (4). Again, changes in associations at different points in time have not been reported previously, but our results in men suggest that disparities between current smokers and never smokers are diminished as levels of central obesity rise among the never smokers.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…A recent large cohort study in the Chinese adult population has also shown that tobacco smoking is an important risk factor for central obesity. However, the positive association of regular smoking with WC was observed especially in male normal-weight adults after adjustment for BMI (4). Again, changes in associations at different points in time have not been reported previously, but our results in men suggest that disparities between current smokers and never smokers are diminished as levels of central obesity rise among the never smokers.…”
Section: Discussioncontrasting
confidence: 52%
“…With some exceptions indicating no association (3), the majority of studies on this topic have found negative associations between current smoking -especially moderate and heavy smoking-and general obesity (2,4,13,26,27). No previous studies have looked at changes in associations coinciding with shifts in the prevalence of obesity and smoking over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations